A comparison of clinical outcomes of acute testicular torsion between prepubertal and postpubertal males. Issue 6 (December 2019) - Goetz, J.; Roewe, R.; Doolittle, J.; Roth, E.; Groth, T.; Mesrobian, H.-G.; Rein, L.E.; Szabo, A.; Kryger, J.
Summary: Short introduction/background: Surgical intervention for acute testicular torsion can require either orchiopexy or orchiectomy. The decision of which surgery to perform is dependant on the amount of time that the testicle experienced ischemia and the viability of the testicle after reperfusion. Objective: It is hypothesized that (1) there is a difference in orchiectomy and orchiopexy rates between prepubertal and postpubertal males with acute testicular torsion and (2) presenting symptoms may vary between the two age groups as prepubertal males may present with atypical symptoms, which could result in delayed presentation and diagnosis. Study design: A retrospective chart review was conducted on pediatric patients who were diagnosed with acute testicular torsion between June 2010 and August 2017. Demographic and clinical characteristics were extracted: age, ethnicity, referral pattern, primary insurance status, symptoms at presentation, prior history of ipsilateral testicular pain or intermittent torsion, recent trauma to genitalia, duration of symptoms (hours), gradual vs. acute onset of symptoms, time/weekday/season at presentation, and time interval from arrival at the study institution to surgical intervention (minutes). Patients were categorized into two groups: prepubertal group (age 1–12 years) and postpubertal group (age 13–18 years). Statistical analyses were performed using R, version 3.3.1. Results: Ninety-one patients were included in the study. The overall orchiectomy rate was 30.8%. More prepubertal males underwent orchiectomy than postpubertal males (42.4% vs. 24.1%, respectively). Prepubertal males were more likely to present with abdominal pain than postpubertal males (27.3% vs. 10.3%, respectively). Those who underwent orchiectomy were more likely to present with longer duration of symptoms, testicular swelling, and abdominal pain than those who underwent orchiopexy. The risk of orchiectomy decreased by 14% per 1-year increase in age (odds ratio [OR]: 0.86, 95% confidence interval [CI]: 0.94–1.00, p = .009). A steady decline in the proportion of patients undergoing orchiectomy was seen from 1 to 12 years of age. Discussion: This study found that prepubertal males are at higher risk for orchiectomy than postpubertal males. The risk of orchiectomy decreases by 14–16% per 1-year increase in age. Prepubertal males are more likely to present with atypical symptoms and delayed presentation and diagnosis, leading to delayed surgical intervention. It is important for providers to perform a genital examination in prepubertal males who present with abdominal pain to rule out acute testicular torsion. Patients presenting with longer duration of symptoms, testicular swelling, and abdominal pain are at higher risk for orchiectomy. No correlation was found between orchiectomy rate and ethnicity, referral status, primary insurance status, and time/weekday/season at presentation. Conclusion: Among patients presenting to a tertiary pediatric hospital with acute testicular torsion, prepubertal males (younger than 12 years) are at higher risk for orchiectomy than postpubertal males. Prepubertal males are more likely to present with atypical symptoms which results in delayed presentation and diagnosis, leading to delayed in surgical intervention.